Analisa Perancangan Nozzle Low-Pressure Sootblower Tipe Long Retractable Pada Boiler PLTU Subcritical - Ika Yuliyani; Ilzam Multazam Ramadan (Fluida, 2025)
Conventional high-pressure sootblowers (148 bar, 492°C) in coal-fired power plants frequently suffer from mechanical failures (e.g., valve leaks, pipe erosion) and excessive energy consumption due to pressure drops. These issues necessitate an alternative solution to improve boiler efficiency and reduce maintenance costs. This study designs a retractable low-pressure nozzle utilizing intermediate-pressure turbine steam (12.13 bar, 395°C) to address these challenges. Through the development of a divergent full-cone nozzle (throat/exit diameters: 15.45/35.87 mm) and verification via Computational Fluid Dynamics (CFD) simulations, the nozzle achieved supersonic flow characteristics (Mach 1.2–1.7) with a steam mass fraction of 99.99%, while reducing pressure drop by 67% (4.77 bar compared to the conventional 14.8 bar). Field tests conducted at PLTU Banten 2 Labuan confirmed an effective cleaning area of 1.028 m² at a distance of 2.135 meters, demonstrating superior performance compared to traditional systems. Furthermore, the system achieved potential annual savings of approximately $3,981 per unit through reduced energy and maintenance costs. The results demonstrate that this low-pressure nozzle design not only mitigates slagging and fouling with lower operational risks but also offers a sustainable, energy-efficient, and economically viable alternative for improving the performance and reliability of subcritical coal-fired boilers.